(untitled) (JURNAL LENTERA ILMIAH PENGABDIAN MASYARAKAT, 2026)
Pregnancy is a physiological condition that may develop into a high-risk situation if appropriate care and management are not provided. Family involvement, particularly that of husbands, plays a crucial role in supporting maternal health and preventing complications during pregnancy and childbirth. This community service program aimed to improve family preparedness in preventing and managing pregnancy-related risks through the Husband Alert (Suami Siaga) Program in Wolasi District, Southeast Sulawesi, Indonesia. The program employed an educational and participatory approach involving pregnant women and their husbands as participants. The implementation consisted of three stages: preparation, health education activities, and evaluation. Educational materials covered pregnancy danger signs, birth preparedness, referral planning, and the role of husbands in supporting maternal health. Evaluation was conducted using pre-test and post-test questionnaires to assess changes in participants’ knowledge. The results demonstrated an improvement in participants’ understanding after the intervention, particularly regarding pregnancy danger signs, birth preparedness, and the importance of husbands’ involvement in maternal health decision-making. In addition, participants showed active engagement and enthusiasm throughout the activities. The Husband Alert Program proved effective in enhancing family preparedness for pregnancy-related risks and can serve as a community empowerment strategy to support efforts aimed at improving maternal and child health outcomes.